Reproductive Health Care for HIV+ Young Women: What Should We Do? - Raymond Surya; Harry Prawiro Tantry; Dwiana Ocviyanti (PT Kalbe Farma Tbk., 2022)
Introduction: This article discusses reproductive health for a young woman with positive HIV during postnatal care. Discussion: In HIV-positive patients, ART treatment protocols may vary. Hormonal contraception in combined oral contraception (COC), progestin-only pill, depo-medroxyprogesterone acetate (DMPA), and implant are considered safe. An intrauterine device (IUD) is also safe for positive HIV women. Cervical cancer screening with Pap smear is performed at the initial diagnosis of HIV in patients less than 30 years of age. Summary: Antiretroviral therapy should be initiated early. HIV patients can safely use either hormonal contraception or an IUD. Cervical cancer screening should be performed at the initial diagnosis of HIV. Pendahuluan: Artikel ini mendiskusikan kesehatan reproduksi wanita muda HIV positif selama perawatan pasca-melahirkan. Diskusi: Pada pasien positif HIV, protokol terapi antiretrovirus cukup bervariasi. Kontrasepsi hormonal dalam bentuk pil oral kombinasi (POK), pil berbasis progestin, depo-medroxyprogesterone acetate (DMPA), dan implan aman untuk pasien HIV positif. Alat kontrasepsi dalam rahim (AKDR) juga aman untuk perempuan HIV positif. Skrining kanker serviks dengan Pap smear sebaiknya dilakukan saat awal terdiagnosis HIV pada pasien usia <30 tahun. Simpulan: Terapi antiretrovirus sebaiknya dimulai sedini mungkin. Pasien HIV aman menggunakan kontrasepsi hormonal maupun AKDR. Skrining kanker serviks sebaiknya dilakukan saat awal terdiagnosis HIV.